Understanding scientific creativity: an exploratory creativity scale for organic chemistry - Blue, Connor; Barr, Nathaniel; Ma, Baldwin; He, Helena; Cox, Charles T.; Seli, Paul (Frontiers in Education, 2025)
Creativity is pivotal for innovation across various domains, including science, technology, engineering, and mathematics (STEM). The present study explores domain-specific creativity in organic chemistry by introducing the Divergent Skeletal Formula Task (DSFT) as a novel measure. The DSFT requires participants to generate constitutional isomers of a given molecular formula, providing an objective quantification of creativity based on the rarity and originality of responses. We investigated the correlations between DSFT performance and established creativity indices—the Alternate Uses Task (AUT) and the Divergent Association Task (DAT)—while controlling for age, gender, and fluid intelligence through partial correlation analyses. The results revealed that correlations between DSFT performance and both AUT Creativity and DAT scores were not statistically significant. However, there was a significant positive correlation between DSFT performance and AUT Flexibility, suggesting that cognitive flexibility is a critical component of creativity in chemistry, even when statistically accounting for age, gender, and fluid intelligence. This finding supports the idea of domain-generality in creativity, indicating that cognitive processes underlying general creative thinking, particularly flexibility, are applicable to specific STEM domains like organic chemistry. Thus, insights from studies on general creativity may be valuable for understanding and fostering creativity in specialized fields, offering practical implications for educational and research settings.